Formulasi Mi Bebas Gluten dengan Bahan Dasar Tepung Umbi Bit (Beta Vulgaris L.) dan Tepung Bayam (Amaranthus Sp.) sebagai Sumber Zat Besi - Eva Kurnia Sofiani; Umar Hidayat; Chairunisa Nur Rarastiti (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Iron deficiency is one of the main causes of anemia, especially in women of childbearing age who have higher iron requirements. Preventive efforts can be done through functional food innovations based on natural iron sources. Beetroot (Beta vulgaris L.) and red spinach (Amaranthus sp.) are known to contain iron in high amounts so they have the potential to be used as alternative raw materials in the manufacture of gluten-free noodles. This study aims to determine the effect of beetroot flour and red spinach flour formulations on the organoleptic properties (color, aroma, taste, and texture) and iron content of gluten-free noodle products. The study used an experimental method with a Completely Randomized Design (CRD) consisting of four treatments: F0 (control), F1 (50:50), F2 (75:25), and F3 (25:75). Iron content analysis was carried out using the Atomic Absorption Spectrophotometry (AAS) method, while the organoleptic test involved 25 untrained panelists who were women aged 15–24 years. The results showed that treatment F3 produced the highest iron content of 12.092 ± 1.658 mg/100 g, while F2 achieved the highest sensory acceptability. Nevertheless, formulation F3 was determined to be the best formulation due to its optimal iron content. This gluten-free noodle product based on beetroot and red spinach has the potential to be developed as a functional food to prevent iron deficiency anemia in women of childbearing age.